Effects of Gait Treatment With a Single-Leg Hybrid Assistive Limb System After Acute Stroke: A Non-randomized Clinical Trial - Watanabe, Hiroki; Marushima, Aiki; Kadone, Hideki; Ueno, Tomoyuki; Shimizu, Yukiyo; Kubota, Shigeki; Hino, Tenyu; Sato, Masayuki; Ito, Yoshiro; Hayakawa, Mikito; Tsurushima, Hideo; Takada, Tomoya; et al. (Frontiers in Neuroscience, 2020)
We hypothesized that a single-leg version of the Hybrid Assistive Limb (HAL) system could improve the gait and physical function of patients with hemiparesis following a stroke. In this pilot study, we therefore compared the efficacy of HAL-based gait training with that of conventional gait training (CGT) in patients with acute stroke. Patients admitted to the participating university hospital were assigned to the HAL group, whereas those admitted to outside teaching hospitals under the same rehabilitation program who did not use the HAL were assigned to the control group. Over 3 weeks, all participants completed nine 20 min sessions of gait training, using either HAL (i.e., the single-leg version of HAL on the paretic side) or conventional methods (i.e., walking aids and gait orthoses). Outcome measures were evaluated before and after the nine training sessions. The Functional Ambulation Category (FAC) was the primary outcome measure, but the following secondary outcome measures were also assessed: National Institutes of Health Stroke Scale, Fugl–Meyer Assessment (Lower Extremity), comfortable walking speed, step length, cadence, 6-minute walk distance, Barthel Index, and Functional Independence Measure. In total, 22 post-stroke participants completed the clinical trial: 12 in the HAL group and 10 in the CGT group. No serious adverse events occurred in either group. The HAL group showed significant improvement in FAC after nine sessions when compared with the CGT group (P = 0.014). However, secondary outcomes did not differ significantly between the groups. Our results demonstrate that HAL-based gait therapy may improve independent walking in patients with acute stroke hemiplegia who are dependent on ambulatory assistance. A larger-scale randomized controlled trial is needed to clarify the effectiveness of single-leg HAL therapy.